Exploring Ride-Sourcing Usage Among Older Adults: A Case Study of DKI Jakarta - Raditya Praja Pamungkas; I Gusti Ayu Andani (The Directorate for Research and Innovation, Institut Teknologi Bandung, 2026)
Mobility is a critical determinant of the quality of life for older adults, particularly in urban areas where limited physical capacity and economic constraints reduce their accessibility to transportation. Ride-sourcing services offer more flexible and independent mobility options; however, their adoption among older adults remains limited due to technological barriers and concerns regarding safety and security aspects. This study explored ride-sourcing usage among older adults in DKI Jakarta and identified the factors influencing their adoption. A quantitative approach was employed using revealed preference survey data collected from 408 older adult respondents. The dataset covered socioeconomic characteristics, health condition, technology response, safety and security perceptions. Descriptive statistics, factor analysis (principal component analysis), and discrete choice modeling (multinomial logit and nested logit) were conducted to analyze user preferences and identify significant factors. The findings indicate that while most older adults have positive perceptions on smartphones, many still require assistance in booking ride-sourcing services, and the majority are classified as inactive users. The nested logit model reveals a potential behavioral transition from assisted booking to independent usage. PCA reduced 28 perception indicators into six factors: driver safety and behavior, trip support, driver characteristics, technological barriers, travel risk, and personal security risk. Discrete choice models identified age, gender, employment status, vehicle ownership, presence of young dependents, physical condition, and user perceptions as significant predictors of ride-sourcing usage.